MFSD12 promotes proliferation, metastasis and invasion of hepatocellular carcinoma cells and its potential correlation with HAVCR2/LGALS9 immune checkpoint axis - Sun, Kai; Wen, Song; Guo, Shou-jun; Pan, Qing-hua; Wang, Ke-run (Frontiers in Immunology, 2025)
BackgroundMajor Facilitator Superfamily Domain-containing 12 (MFSD12) has emerged as a critical transmembrane protein with increasingly recognized roles in various cancers. The complex pathogenesis and therapeutic resistance of liver hepatocellular carcinoma (LIHC) present significant clinical challenges. This study investigates MFSD12’s potential involvement in LIHC progression.Methods and resultsWe performed an extensive pan-cancer analysis of MFSD12 utilizing integrated datasets from The Cancer Genome Atlas (TCGA), the Gene Expression Omnibus (GEO), and the ArrayExpress database. Our investigation focused on evaluating its prognostic significance, clinical implications, associated signaling pathways, immune cell infiltration, gene mutations, and sensitivity to chemotherapeutic agents. Through the application of R and various online analytical tools, our study demonstrated that MFSD12 expression levels were significantly higher in LIHC compared to other cancer types within the TCGA pan-cancer dataset. This finding highlights the specificity of MFSD12 expression in LIHC, a conclusion further validated by immunohistochemical analysis. Survival analysis indicated that this upregulation is associated with unfavorable clinical outcomes. Furthermore, single-cell RNA sequencing revealed that MFSD12 was predominantly expressed in tumor cells and innate lymphoid cells (ILCs) within the tumor microenvironment. Functional vitro studies showed MFSD12-siRNA treatment effectively suppressed LIHC cell proliferation, migration, and invasion. Mechanistically, MFSD12-siRNA enhanced E-cadherin while reducing vimentin, MMP-2, and MMP-9 levels. Further analyses revealed significant associations between MFSD12 expression and immune infiltration, immune checkpoint molecules, tumor mutation burden, and microsatellite instability in LIHC. Notably, MFSD12-siRNA decreased HAVCR2(TIM3) and its ligand galectin-9 (LGALS9) expression in LIHC cells.ConclusionsOur findings demonstrated that MFSD12 upregulation in LIHC strongly correlates with poor prognosis. This association was potentially attributed to MFSD12’s dual roles: promoting tumor cell proliferation, migration, and metastasis while critically modulating the tumor immune microenvironment, particularly through interaction with the HAVCR2/LGALS9 immune checkpoint axis.